Trade development policies and the post-2015 sustainable development agenda, and formulation of national policies in the context of existing regional trade agreements (UN New YorkUS, 2015)
Discusses the importance of, and challenges in, designing and implementing at the national level an integrated policy mix, of which trade policy is a key component. Looks at the impact regional trade agreements may have on the formulation of national development policy and the need for a global partnership that would support and reinforce national efforts and combine them towards achieving the future we want. Suggests some issues that can be discussed with regard to national actions that can be taken at the national, regional and global levels.
Note by the UNCTAD Secretariat.